Investigating the Challenges and Complexities of Conducting Research: Viewpoint of Undergraduate Students at Al-Istiqlal University - Khaled M S Masood, Nawal Al-Sheikh (International Journal of Advanced Science and Technology, 2020)
The purpose of this study was to recognize the size of the administrative, technical (scientific & pedagogic), and linguistic problems facing cadets who study the Research Methodology Course in all the programs at Al-Istiqlal University from cadets` perspective according to their gender and specialization. The study was conducted on 219 students of the Research Methodology Course in the first semester of the academic year 2019/2020. A questionnaire was developed by the researchers to collect the sample opinions on the challenges and complexities of conducting research work. The descriptive-analytical methodology was adopted for this study. The study concluded that the biggest administrative problems facing students in studying the Research Methodology Course were the inability to access the library in the evening period after the end of lectures and military training, the lack of any prior experiences in practicing research, and the high load of courses including the Research Methodology Course the students registered for in the semester. Concerning the technical (scientific & pedagogic) problems, it is found that students face weakness in using the appropriate statistical methods, as well as differentiating between types of research. In connection with linguistic problems, it is found that students are weak in applying Arabic and English grammatical rules. However, gender and specialization variables do not affect the size of the problems the students face in the course. The results highlight the administrative, technical, and linguistic problems students face in conducting research work